Comparative Evaluation of Disinfection on Elastomeric Impression Material using 2% Gluteraldehyde, Ultra Violet Radiation and Gaseous Ozone using Customised Disinfection Unit - An In-Vitro Study - Hetal Purohit; Sweta Kale Pisulkar; Seema Sathe Kambala; Surekha Dubey Godbole; Chinmayee Dahihandekar; Rohit Ashok Mistry (Indian Journal of Forensic Medicine & Toxicology, 2021)
Dental impressions is the preliminary step for any procedure and acts as a microbial source leading to contamination to the operator and lab technician. Hence, the disinfection of these impressions materials should be carried out unfailingly. The device was fabricated which helped in easy and effective disinfection.Aim: The aim of the study is to Compare and Evaluate the Efficacy of Disinfection on Elastomeric Impression material using 2% Gluteraldehyde, UV Radiation Disinfection and Gaseous Ozone. Objective: The efficacy of the disinfectants was compared based on the ability of the disinfectants in reducing the microbial colonies on the impression material. Methodology: Microbiological analysis was done and the colony forming units were evaluated and compared. The disinfection was done with a customized disinfection chamber which can be readily installed in the clinic and has multitudes of use other than disinfection. Result: Dry Gaseous Ozone as a disinfectant proved to be efficacious as compared to the other disinfectants. Conclusion: Dry gaseous ozone can be used effectively for disinfection of impressions without altering its dimensional stability. The customized disinfection unit is portable and can be readily installed in the clinic.